Overview of Bacterial Patterns in Diabetic Ulcer Patients at Gatot Soebroto Army Hospital and Fatmawati General Hospital and The Review According to Islamic Perspective - Achya, Vioni Alvida; Eliana, Fatimah; Gunawan, Andri (Fakultas Kedokteran Universitas YARSI, 2023)
Background: Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. Complications of this disease are diabetic foot ulcers. Diabetic foot ulcer is an ulcer that occurs on the leg of a DM patient. One of the risk factors for diabetic foot ulcers is infection. Many diabetic foot ulcers are caused by Staphylococcus aureus and Pseudomonas spp. Method: This study used secondary data from medical records of bacterial culture of diabetic ulcer patients at the Gatot Soebroto Army Hospital and Fatmawati General Hospital from January 2018 to December 2021. Results: There are 10 most common types of bacteria at Gatot Soebroto Army Hospital, namely Escherichia Coli, Klebsiella Pneumoniae, Citrobacter Koseri, Enterobacter Aerogenes, Staphylococcus Aureus, Enterococcus Faecalis, Proteus Mirabilis, Proteus Hauseri, Streptococcus Agalactiae and Cupriavidus Pauculus. At Fatmawati General Hospital, the highest number of 10 types of bacteria were found, namely Escherichia Coli, Klebsiella Pneumoniae, Acinetobacter baumannii, Pseudomonas Aeruginosa, Enterococcus Faecalis, Proteus Mirabilis, Staphylococcus Haemolyticus, Serratia Liquefaciens, Proteus Pennerii, and Providencia Rettgeri.Conclusion: The most common bacteria found in the two hospitals are Escherichia Coli and Klebsiella Pneumoniae. In the view of Islam, Rasulullah shallallahu alaihi wa salam gives an example of a person who is healthy in body and soul as the owner of the whole world and its contents.